MODEL PENGEMBANGAN KARIR DOSEN WANITA BERPERAN GANDA - Nurul Fitrianingrum (Department of Management, Faculty of Economics, Universitas Islam Sutan Agung, Semarang, 2017)
The purpose of this study is to describe and analyze the effect on work motivation, familyand social support dual role conflict to career development. Data were obtained from femalelecturers Unissula Semarang using a questionnaire by 67 respondents. The sampling techniqueusing non-random sampling method. Data analysis method used is multiple linear regression.The results of this study indicate that work motivation variable significant effect on careerdevelopment, family support significant effect on career development, while the dual role conflictno significant effect on career development. Work motivation no significant effect on the conflictof roles, family support does not significantly influence conflict dual role. However, motivationand family support direct effect on career development.Keywords: Motivation Work, Social Support Family, Dual Role Conflict, and Career Development.